A bio-inspired model of organizational excellence. Issue 2 (1st August 2016) - Agarwal, Alpana; Vrat, Prem
Abstract : Purpose: The aim of this paper is to validate the enablers of bio-inspired model of organizational excellence proposed by Agarwal and Vrat (2015). It is also aimed to test its usefulness as an instrument in evaluating the degree of organizational excellence achieved. Design/methodology/approach: Survey methodology has been used to investigate the hypotheses. Data have been collected through a self structured questionnaire with closed-ended questions. Structural Equation Modeling (SEM) and Analytic Hierarchic Process (AHP) have been used to test and analyze the data. Findings: The results of hypothesis testing indicated that out of 19 paths only 10 were significant. However in the revised model only 6 paths out of those 10 significant paths were retained and 3 new suggested paths were incorporated to make the final model. Besides, calculation of relative weights of each enabler, shows that being self driven occupies the top-most rankings, supply chain optimization occupies the second rank and promptness and reliability & maintainability occupy the bottom ranking in driving performance excellence, being resulting outcomes. Research limitations/implications: The major limitations of this research are: verification of the proposed model is done on only two test companies, and results of which are compared with one excellence award model only. Besides, the score resulted for test companies are based on self assessment by them and thus require further validation. Practical implications: The validated model can be applied for assessing degree of organizational excellence achieved by any company. The results of the assessment would serve as key focus areas for improvement. Originality/value: The research is first to benchmark the human body for assessing the degree of organizational excellence achieved. The uniqueness of this model is that the various parameters of excellence assessment which are derived from human body, perceived as a benchmark in being the most well managed system.